Sericin-Enriched Rabbit Semen Preservation: Implications for Short-Term Storage Quality and Fertility at 4 or 15 °C - Sanan Raza; Uğur Uçan; Melih Aksoy; Güneş Erdoğan; Zahid Naseer; Komal Khan (Animals)
The influence of sericin supplementation and chilling temperatures (4 and 15 °C) on the short-term storage quality and fertility of rabbit semen was assessed over 72 h of storage. In experiment 1, pooled semen (five replications) was diluted to a concentration of 50 M mL−1, and assigned to control, 0.1%, and 0.5% sericin groups, stored at 4 or 15 °C. Sperm motility, sperm kinematics, viability, and membrane and acrosome integrity were assessed at 0, 24, 48, and 72 h of storage. Experiments 2 and 3 were conducted to observe the effect of sericin on bacterial growth and in vivo fertility. The results of experiment 1 showed that sericin treatment, storage temperature, and storage duration influenced progressive and total sperm motility. The storage duration affected all sperm kinematics variables, whereas VCL, VSL, VAP, and BCF sperm kinematics altered in response to sericin treatment and storage temperature. Similarly, significant effects of sericin treatment, storage temperature, and storage duration were observed for acrosome integrity, sperm membrane integrity, and sperm viability. The results of experiment 2 indicated the antimicrobial effects of sericin when sperm were stored at 15 °C for 72 h. While promising pregnancy outcomes were observed with sericin-treated sperm for 72 h, these results were not significantly different. This study conclusively demonstrates that sericin treatment enhances the quality of rabbit semen when stored at lower temperatures for longer durations. The antimicrobial effects of sericin could be a contributing factor to the improved in vitro and in vivo fertility of rabbit sperm.